Regulated to respond: dual localization and dynamic control of AVP1 in plant carbon partitioning - Gaxiola, Roberto; Hirschi, Kendal D. (Frontiers in Plant Science, 2025)
Arabidopsis Vacuolar Pyrophosphatase 1 (AVP1), a conserved type I proton-pumping pyrophosphatase (H+-PPase), was characterized as tonoplast localized with a role in acidifying the lumen and removing cytosolic pyrophosphate (PPi), a byproduct of biosynthesis. During the last several decades evidence has accumulated that AVP1also localizes to the plasma membrane, particularly in phloem companion cells, where it may function in reverse—synthesizing PPi from the proton motive force. This directional flexibility allows AVP1 to contribute to intracellular homeostasis and to phloem loading, supporting carbon partitioning from source to sink tissues. AVP1 activity is modulated post-translational through ubiquitin-dependent turnover, enabling plants to adjust in response to metabolic conditions. AVP1’s localization, regulation, and metabolic integration position it as a coordinator of energy balance. These features highlight AVP1 as a focal point for future approaches focused on crop resource-use efficiency and climate resilience.